1999
DOI: 10.1016/s0735-1097(98)00634-2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, clinical and etiologic features, and outcomes of advanced chronic heart failure: the EPICAL study

Abstract: Mortality and hospitalization rate of advanced CHF remain very high despite recent therapeutic progress. Major therapeutic and managed-care research is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
151
0
11

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(175 citation statements)
references
References 34 publications
13
151
0
11
Order By: Relevance
“…One-year mortality rates in population-based studies have been reported to be 25% to 45%. [2][3][4][5] The mortality rate was higher in heart failure with reduced ejection fraction (HFrEF) than heart failure with preserved ejection fraction (HFpEF). 6) Mortality rates of HFrEF (ejection fraction < 50%) patients were reported to be 32% at one year and 68% at 5 years.…”
mentioning
confidence: 99%
“…One-year mortality rates in population-based studies have been reported to be 25% to 45%. [2][3][4][5] The mortality rate was higher in heart failure with reduced ejection fraction (HFrEF) than heart failure with preserved ejection fraction (HFpEF). 6) Mortality rates of HFrEF (ejection fraction < 50%) patients were reported to be 32% at one year and 68% at 5 years.…”
mentioning
confidence: 99%
“…This allowed us to analyze the sympathetic activation of HF and suppose, considering that this study is not randomized and that high heart rates are associated with a worse prognosis in cardiovascular disease, although it is examination physical data poorly described in publications. The same was confirmed in the study EPICAL 18 , in which heart rate was identified by multivariate analysis as an independent predictor of death, both in ischemic heart disease and in dilated cardiomyopathy 17,19 . Serum creatinine was also an independent predictor of cardiovascular mortality and very much related with the prognosis (HR: 1.17 for each 1 mg/dl, p=0.005), so we chose to use the ROC curve to select the best cutoff point.…”
Section: Survival Analysismentioning
confidence: 52%
“…Another variable that was considered a predictor of survival by the multivariate model of survival was age, also present in other studies 19,[22][23][24][25] . For each additional ten years of age, the prognosis was worse, with HR: 1.37 and p < 0.001.…”
Section: Survival Analysismentioning
confidence: 83%
“…Hypertension Braunstein et al [6] 55% had HT and 11% severe HT in the Medicare study (n=122,630 patients) Ho et al [7] 39% of men and 59% of women had HT in the Framingham study Levy et al [8] Gustafsson et al [9] 27% of the men and 22% of the women had HT in the Danish Diamond study (n=5491 patients) Himmelman [10] At least 50% of patients with HT develops HF Diabetes Kannel et al [24] Risk for developing HF in young males and females with DM (2.20 and 5.37, respectively) Shindler et al [25] In the SOLVD study 15% in the prevention trial and 26% in the treatment trial had DM Cohn et al [26] Similar results in the V-HeFT II trial (26%) had DM CONSENSUS trial [27] 23% developed DM in the CONSENSUS trial Rydén et al [28] 19% developed DM in the ATLAS study Shindler et al [25] In the SOLVD registry (n=6076 patients) 23% had DM Zannad et al [29] In the French registry study EPICAL 26% had DM Braunstein [6] In the Medicare study (n=122,630 patients) 31% had DM Stratton et al [30] Interrelationship between HbA1c levels and incidence of HF Iribarren et al [31] Each 1% increase in HbA1c was associated with 8% increased risk of developing HF Paolisso et al [32] Whole body insulin resistance is prevalent in HF patients with either ischemic or idiopathic dilated cardiomyopathy Swan et al [33] Similar results as in Paolisso…”
Section: Study Resultsmentioning
confidence: 86%